The Social Path to Brand Loyalty: How Interaction and Relationships Drive Commitment in Brand Communities - Indah Fatmawati; Aji Listyo Raharjo (International Journal of Science, Technology & Management, 2026)
Brand communities have become an important strategic platform for strengthening consumer–brand relationships and fostering long-term loyalty. However, empirical evidence explaining how experiential and social dynamics within brand communities translate into brand loyalty remains limited. This study investigates the effects of experience, individual interaction, and social relationships on brand loyalty, with community commitment as a mediating variable, among particular DSLR camera brand users in Yogyakarta, Indonesia. A quantitative approach was employed using survey data from 150 members of photography communities. The data were analyzed using Structural Equation Modeling (SEM) with AMOS 22. The findings reveal that individual interaction and social relationships significantly enhance community commitment, whereas experience does not. Furthermore, community commitment has a strong positive effect on brand loyalty and serves as a mediator in the relationships among experience, individual interaction, and social relationships. This study highlights the critical role of social interaction and relational bonding in brand communities as key drivers of consumer loyalty. The findings provide managerial insights for firms seeking to leverage brand communities as strategic tools for relationship marketing and customer retention.